Synthesis of Substituted Tropones by Sequential Rh-Catalyzed [5+2] Cycloaddition and Elimination - Song, Wangze (Tetrahedron, 2015)
Highly substituted tropones are prepared from cycloheptatrienes derived from Rh-catalyzed intermolecular [5+2] cycloaddition of 3-acyloxy-1,4-enynes and propargylic alcohols. The intermolecular [5+2] cycloaddition is highly regioselective for a variety of propargylic alcohols. Elimination of the cycloaddition products afforded various substituted tropones.